1995
DOI: 10.1111/j.1469-8137.1995.tb04296.x
|View full text |Cite
|
Sign up to set email alerts
|

The growth and gas exchange response of soil‐planted Norway spruce [Picea abies (L.) Karst.] and red oak (Quercus rubra L.) exposed to elevated CO2 and to naturally occurring drought

Abstract: SUMMARY Norway spruce and red oak trees were planted directly into the soil and exposed to 700 μmol mol‐1 CO2 in open‐top chambers. There were large inter‐specific differences in response to naturally occurring drought during the second year of exposure to elevated CO2. Both species had decreased assimilation rates. CO2‐treated red oak had no loss of photosynthetic enhancement when undroughted, whereas CO2‐treated Norway spruce showed a relative increase in assimilation rates only when draughted. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…Teskey 1997) but not in others (Bunce 1992, Dixon et al 1995, Atkinson et al 1997. The mitigation of the effects of water stress by EC was reflected in the aboveground biomass growth in 1998.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Teskey 1997) but not in others (Bunce 1992, Dixon et al 1995, Atkinson et al 1997. The mitigation of the effects of water stress by EC was reflected in the aboveground biomass growth in 1998.…”
Section: Discussionmentioning
confidence: 94%
“…The interactive effects of drought and rising C a are considered crucial for the prediction of the responses of forest trees to the global environmental change (Beerling et al 1996, Norby andLuo 2004). Many studies on the responses of trees to elevated C a (EC) under water stress have been reported (Morison 1993, Dixon et al 1995, Roden and Ball 1996, Anderson and Tomlinson 1998, but most of these studies were carried out with seedlings under controlled environment and only relatively short-term C a enrichment. There are several differences in the field compared to controlled environment regarding drought: (a) Drought stress evolves more gradually in the field and plants experience no root constriction from confinement in pots (Lawlor and Mitchell 1991, Ceulemans and Mousseau 1994, Körner 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Clifford et al, 1995;Heckenberger et al, 1998;Pa Èa Èkko Ènen et al, 1998). Some studies, however, report no response (Estiarte et al, 1994;Dixon et al, 1995;Pritchard et al, 1998;Centritto et al, 1999). No studies report a decrease.…”
Section: Water Stressmentioning
confidence: 99%
“…While decreased stomatal conductance is a common response to elevated CO 2 (Eamus and Jarvis, 1989), and lower conductance (or leaf transpiration rate ) in elevated CO 2 has been reported for Q robur (Picon et al, 1996a), Q petraea (Picon et al, 1995b), and Q alba (Norby and O'Neill, 1989), in other studies there was no effect of CO 2 on stomatal conductance of Q prinus, Q robur (Bunce, 1992), or Q rubra (Dixon et al, 1995). Photosynthetic CO 2 assimilation was increased by elevated CO 2 in Q alba (Norby and O'Neill, 1989), and this response, along with a lower transpiration rate, contributed to an increase in water-use efficiency measured both at the leaf level and at the wholeplant level.…”
mentioning
confidence: 95%
“…Leaf-level responses Responses to CO 2 are also measured at the leaf level. Stomatal density of herbarium specimens of Q robur (Beerling and Chaloner, 1993) and Q ilex (Paoletti and Gellini, 1993) or Q rubra (Dixon et al, 1995).…”
mentioning
confidence: 99%